Test on shear behavior of less-tightened high-strength bolted connections. (December 2021) - Lin, Quan; Xue, Xiaolei; Guo, Zhan; Zhao, Yang; Chen, Yu
Abstract: This paper conducts an experimental study on the mechanical properties of less-tightened high-strength bolted connections composed of 8 bolts under the action of double shear. 63 groups of connections were tested in the experiment, of which 60 groups were tested in different percentage reduction of clamping force and the other three groups were tested with standard clamping force as control groups. The effects of the percentage reduction of clamping force of less-tightened bolts, the number of less-tightened bolts, and the thickness of core plate on the bearing behavior of bolted connections were analyzed. The effects of the three parameters on the failure mode, strain distribution, slip resistance, ultimate bearing capacity, ductility, and initial stiffness of bolted connections are studied. As can be seen from the failure mode, all specimens showed bolt damage, which was cut off on one side and twisted on the other side. The test results revealed that the decrease of clamping force exerts a negative impact on the slip resistance, and the ultimate bearing capacity of less-tightened bolted connections. These capacities of the specimens are reduced significantly with the increase of the percentage reduction of clamping force and the number of less-tightened bolts, while the thickness of the core plate has slight effect on these performances. In addition, with the decrease of the clamping force, the ductility of the specimen increases, while the increase of the thickness of the core plate will decrease the ductility of the specimen. Further, the influence of these factors on the initial stiffness of the specimens can't be ignored. By comparing with specifications, the modified formula of ultimate bearing capacity of bolted connections with reduced clamping force is put forward.